2013
DOI: 10.1093/ndt/gft502
|View full text |Cite
|
Sign up to set email alerts
|

ABO antibody and complement depletion by immunoadsorption combined with membrane filtration--a randomized, controlled, cross-over trial

Abstract: We demonstrate that the innovative strategy of combining MF with semi-selective IA may substantially increase IgM elimination and affect classical complement activation. Our findings suggest that this new treatment concept could be an efficient strategy for recipient desensitization in ABO- and HLA-incompatible transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 32 publications
0
48
0
3
Order By: Relevance
“…In contrast, unselective IA was less effective in the removal of anti-A/B antibodies of the IgM (74 versus 30%, P  < 0.001) and IgG3 subclass (72 versus 42%, P  < 0.05). The same group found that a combination of membrane separation and unselective IA effectively removed IgG and IgM antibodies and effector molecules such as complement C1q component (11). No significant differences were found in clinical studies that compared the impact of different IA strategies on clinical outcomes, including anti-A/B antibody reduction, survival, kidney function, rejection episodes, or complications (12).…”
Section: Desensitization For Aboi Kidney Transplantationmentioning
confidence: 99%
“…In contrast, unselective IA was less effective in the removal of anti-A/B antibodies of the IgM (74 versus 30%, P  < 0.001) and IgG3 subclass (72 versus 42%, P  < 0.05). The same group found that a combination of membrane separation and unselective IA effectively removed IgG and IgM antibodies and effector molecules such as complement C1q component (11). No significant differences were found in clinical studies that compared the impact of different IA strategies on clinical outcomes, including anti-A/B antibody reduction, survival, kidney function, rejection episodes, or complications (12).…”
Section: Desensitization For Aboi Kidney Transplantationmentioning
confidence: 99%
“…12,15,47,48 The system uses microprocessors to monitor all predetermined adsorption and desorption parameters of the adsorbers.…”
Section: Filtration/adsorption Devicementioning
confidence: 99%
“…The advent of extracorporeal therapies, including TPE, DFP, and antigen‐specific immunoadsorption, enable depletion of resident IHs, reducing the chance of AMR . DFP and immunoadsorption have been developed in an attempt to selectively deplete anti‐A and anti‐B IHs void of the disadvantages linked to TPE including hypersensitivity, citrate toxicity, and hemodynamic stress . Although implementation of DFP is largely confined to Japanese centers and immunoadsorption has yet to become broadly utilized in ABO‐ILT, both methods typify alternative options for IH titer reduction with minimized side effects .…”
Section: Strategies For Risk Mitigationmentioning
confidence: 99%